Sustainable Smart Grid Architecture: Carbon Footprint Reduction with Oracle Utilities Software - Rajesh Bonepalli, (International Journal of Scientific Research in Computer Science, Engineering and Information Technology, 2025)
This article examines the implementation of Oracle Utilities Software for reducing carbon footprints in smart grid systems, focusing on the evolution from traditional power distribution networks to intelligent, sustainability-focused infrastructures. The article explores core technical components, including cloud-based analytics, distributed energy resource management, and advanced metering systems, while analyzing implementation strategies for optimal architecture and technical solutions in urban environments. The article investigates performance benefits across environmental impact and operational improvements, highlighting the integration of resilience-based metrics and efficiency gains. It addresses critical implementation challenges and solutions, particularly in developing markets, examining both technical hurdles and organizational considerations. The article culminates in an analysis of future trends and innovations, encompassing emerging technologies such as AI optimization, blockchain integration, and edge computing advances, while exploring industry evolution through sustainability trends and integration opportunities. This article provides valuable insights for utilities and organizations seeking to implement sustainable smart grid solutions while managing environmental impact and operational efficiency.
Keywords: Smart Grid Technology; Carbon Footprint Reduction; Oracle Utilities Software; Renewable Energy Integration; Grid Management Systems